Head and neck oncology during the COVID-19 pandemic: Reconsidering traditional treatment paradigms in light of new surgical and other multilevel risks. (June 2020) - Day, Andrew T.; Sher, David J.; Lee, Rebecca C.; Truelson, John M.; Myers, Larry L.; Sumer, Baran D.; Stankova, Lenka; Tillman, Brittny N.; Hughes, Randall S.; Khan, Saad A.; Gordin, Eli A.
Highlights: The COVID-19 pandemic necessitates reevaluation of head and neck oncology paradigms. There are novel COVID-19-specific barriers to safe head and neck surgery. There are substantial multilevel risks to patients, health care workers and society. Multidisciplinary assessment of risks and shared decision-making are recommended. In select circumstances, alternatives to surgery should be temporarily considered. Abstract: The COVID-19 pandemic demands reassessment of head and neck oncology treatment paradigms. Head and neck cancer (HNC) patients are generally at high-risk for COVID-19 infection and severe adverse outcomes. Further, there are new, multilevel COVID-19-specific risks to patients, surgeons, health care workers (HCWs), institutions and society. Urgent guidance in the delivery of safe, quality head and neck oncologic care is needed. Novel barriers to safe HNC surgery include: (1) imperfect presurgical screening for COVID-19; (2) prolonged SARS-CoV-2 aerosolization; (3) occurrence of multiple, potentially lengthy, aerosol generating procedures (AGPs) within a single surgery; (4) potential incompatibility of enhanced personal protective equipment (PPE) with routine operative equipment; (5) existential or anticipated PPE shortages. Additionally, novel, COVID-19-specific multilevel risks to HNC patients, HCWs and institutions, and society include: use of immunosuppressive therapy, nosocomial COVID-19 transmission, institutional COVID-19 outbreaks, and, at some locations, societal resource deficiencies requiring health care rationing. Traditional head and neck oncology doctrines require reassessment given the extraordinary COVID-19-specific risks of surgery. Emergent, comprehensive management of these novel, multilevel surgical risks are needed. Until these risks are managed, we temporarily favor nonsurgical therapy over surgery for most mucosal squamous cell carcinomas, wherein surgery and nonsurgical therapy are both first-line options. Where surgery is traditionally preferred, we recommend multidisciplinary evaluation of multilevel surgical-risks, discussion of possible alternative nonsurgical therapies and shared-decision-making with the patient. Where surgery remains indicated, we recommend judicious preoperative planning and development of COVID-19-specific perioperative protocols to maximize the safety and quality of surgical and oncologic care.